Development of an enantioselective amine–silver co-catalyzed Conia-ene reaction. Issue 28 (22nd March 2017) - Blümel, M.; Hack, D.; Ronkartz, L.; Vermeeren, C.; Enders, D.
Abstract : The development of a novel cooperative catalytic system for an amine–silver co-catalyzed Conia-ene reaction of alkyne-tethered C–H-acidic compounds is reported. Abstract : The development of a novel cooperative catalytic system for an amine–silver co-catalyzed Conia-ene reaction of alkyne-tethered C–H-acidic compounds is reported. By using a cost-effective silver salt and a small diamine for the 5- exo-dig -cyclization the cyclopentane products are obtained in very good yields. The enantioselectivity of the reaction could be controlled by exchanging the diamine co-catalyst with a cinchona-derived primary amine.